Kissing the Church Bell or Ringing the Church Bell? (About a verse of the ode of “Tarsaeiyeh”) - Majid Mansouri (مطالعات زبانی و بلاغی)
The famous ode of “Tarsaeiyeh” contains a verse that has puzzled the commentators and proofreaders of Khaqani's collection of poems. The main complexity of the verse in question is the reference that "kissing the church bell" has the ironic meaning of becoming an infidel and leaving the religion of Islam.The main problem in Khaqani's verse is that "kissing the church bell" does not occur in any of the old texts, and unlike kissing the crucifix, "kissing the church bell" was never widespread in Christianity; In addition to the various statements of the commentators of Khaqani's collection of poems, two detailed articles have exclusively dealt with this topic; the first article is about the proposal to correct "Kissing the church bell" to "Drinking the church bell" and the second defends the authenticity of the recording of "kissing the church bell" and rejects the first article. Of course, there is no authentic textual evidence for "kissing the church bell" and "drinking the church bell" in either article. In this study, based on some evidence from Khaqani's collection of poems and other works of Persian literature, it is shown that "I kiss the church bell" in Persian (ناقوس بوسم) in Khaqani's collection of poems is the result of a pun on the "I knock the church bell "in Persian (ناقوس کوبم). In the old spelling, sometimes the writers did not put the stroke of "ک" and "گ"; so the phonemes were easily converted to "ب" and "ت" etc. In another part of the article, "the bell of Magi " is explained and shown that, in Zoroastrian, "the striking of the mortar," was considered as a call to prayer and a sign of invitation to participate in religious ceremonies. Thus, by assigning the bell to Magi, no heresy has taken place, and only the conversion of a proper noun into a common noun has occurred.